2015
DOI: 10.3892/ol.2015.3986
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar liponeurocytoma: A case report and review of the literature

Abstract: Abstract. Cerebellar liponeurocytoma is rare, and the clinical characteristics and treatment strategy remain unclear. In the present study, a case of cerebellar liponeurocytoma was retrospectively reported and a literature review was performed. A 45-year-old female presented due to occipital headaches, exhibiting a hoarse voice and a broad-based gait. Pre-operative magnetic resonance images revealed a lesion occupying the right hemisphere of the cerebellum and the inferior vermis, compressing the medulla oblon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…However, rather than exposing the patients to the risks and side-effects of radiotherapy, without any evidence to support its usefulness in preventing recurrence, we recommend reoperation on a recurrent tumor, which has only a slightly more aggressive histology than the primary presentation, with the option of using adjuvant radiotherapy at this time. 3 Further studies regarding the natural history of this lesion are warranted. 4…”
Section: Discussionmentioning
confidence: 98%
“…However, rather than exposing the patients to the risks and side-effects of radiotherapy, without any evidence to support its usefulness in preventing recurrence, we recommend reoperation on a recurrent tumor, which has only a slightly more aggressive histology than the primary presentation, with the option of using adjuvant radiotherapy at this time. 3 Further studies regarding the natural history of this lesion are warranted. 4…”
Section: Discussionmentioning
confidence: 98%
“…This neoplasm develops predominantly in cerebellar hemisphere and vermis, occasionally in supratentorial lateral ventricle and the fourth ventricle. So far, approximately 47 cases of cerebellar, 11 cases of supratentorial intraventricular and 2 cases of fourth ventricular liponeurocytomas are on record in the English literature [ 5 - 11 ]. Comparing to the liponeurocytoma occurred in cerebellum, little is known about intraventricular liponeurocytoma due to the lower number of reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CLNC is different from medulloblastoma and more similar to neurocytoma but with a distinct genetic pathway due to the presence of TP53 mutations [14]. Moreover, Hirokazu et al [32] reported the absence of both chromosome 1p/19q loss and IDH1 mutation, which might be useful in differential diagnosis of oligodendroglioma [4]. Our tumor showed neither immunohistochemical features of p53 and IDH1 alterations nor SHH and β-catenin activation.…”
Section: Discussionmentioning
confidence: 80%
“…It was first described in 1978 by Bechtel et al [2], and nearly 50 cases under several synonyms have been reported since [11,26,32,33]. In the 2000 World Health Organization (WHO) classification of Tumors of the Central Nervous System it was categorized for the first time as a distinct entity within the neuronal and mixed neuronal-glial tumors section.…”
Section: Introductionmentioning
confidence: 99%